The European dimension in the Turkish history curriculum: an investigation of the views of teaching professionals - Dinç, Erkan (2005)
This study highlights three main concerns in relation to history teaching in Turkish secondary schools. The first one investigates student and practising history teachers' and history teacher educators' views on the existing Turkish secondary school history curriculum and its implementation. The second concern is to explore the perspectives of the same population about Europe and the European dimension in history teaching. The last one deals with their suggestions on the improvement of the history curriculum with the potential inclusion of the European dimension. These issues are considered important, because the recent political developments accelerating the process of Turkey's integration into Europe indicated the necessity for preparing the Turkish public for this purpose. History teaching in schools is one of the channels to prepare Turkish youth to take a part in Europe through developing their perspectives and abilities. The methodological design of the study embraces both quantitative and qualitative research methods. Questionnaires were completed by student teachers, practising teachers and teacher educators from various secondary schools and three universities in Turkey. Semi-structured interviews were carried out with a small number of participants selected from the above three groups. The data are analysed to find out the participants' general views about the issues mentioned above as well as the similarities and differences amongst the views of the three participating groups and between student teacher and teacher educator participants from the three universities. The results of the study show that most of the participants are critical of the existing curriculum and the current practice of history teaching. Their criticism focuses on the presentation of the aims and objectives of the curriculum, the selection of curriculum content and pedagogical problems. According to the research findings, the presentation of Europe and European history in the current curriculum is inadequate. Furthermore, the participants' disclosed varying views about European matters, but their positive views about Europe related issues and a potential inclusion of the ED in history teaching observed were encouraging. Based on the suggestions of the participants, it is argued that the Turkish secondary school history curriculum needs to be improved by including a European dimension. Specifically, the aims and objectives of history teaching, the criteria for the selection of curriculum content, pedagogy and history teacher education programmes should be shifted from the existing traditional approach to the new critical and skill-based approaches. In other words, this study argues that the purpose of history teaching is not to develop a particular identity or citizenship consciousness through the transmission of predetermined content knowledge. Instead, it suggests that history should be taught to enable learners to develop historical and critical thinking skills through exercising and utilising the methodology of history, which help them orientate themselves in local, national, European and global contexts.